Covid-19 and some contours of India's ongoing agrarian crisis. Issue 1 (March 2021) - De Roy, Shantanu; Saratchand, C.
The onset of the Covid-19 pandemic has led to an aggravation of the agrarian crisis in India. The rural proletariat, poor peasants, and a section of middle peasants in India have been adversely affected. The paper advances a composite policy initiative to deal with this aggravation of the agrarian crisis involving an expansion of the existing rural employment guarantee schemes, various input subsidies to farmers, universal provision of safety gear for rural producers, and an expanded public procurement of food grains. It concludes with the political prognosis of the proposed composite policy initiative.